PENGARUH KOMPETENSI, INDEPENDENSI, DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris pada Kantor Akuntan Publik di Provinsi Banten) - Ismiyati, Anna Anica (JURNAL RISET AKUNTANSI TIRTAYASA, 2019)
The objectives of this research to empirically analyze the influence of competency, independency, and acuntability on audit quality, and to the influence of competency, independency, and professionalism to audit  quality  is moderated by auditor ethics, especially in the auditor working in KAP of province Banten.The population in this research are all auditors who worked on the KAP in province Banten. Sampling  was conducted  using jenuh sampling method and number of samples of 103 respondents. Primary data collection method used is questionnaire method. The data are analyzed by using technical analyze Multiple Regression Analyze and Moderate Regression Analyze (MRA). The results showed that the effect on the competence and independence of audit quality, while acuntability has no effect on audit quality. Interaction competence and ethics of auditors, ethics and auditor independence interaction effect has no effect on audit quality, while the interaction of acuntability and ethical auditor on audit quality.  The coefficient of determination shows that jointly competence, independence, acuntabiliy, ethics of auditors, interaction competence and ethics of auditors, ethics and auditor independence interaction and interaction of acuntability and ethical auditor contributed to the dependent variable (quality audit) is 89,8% while the remaining 10,2% is influenced by other factors outside of observation. Keyword: Competency, Independency, Acountability, Auditors Ethics, Quality of Audit.